The Relationship of Transformational and Learning Organization with Teacher Creativity - Apiani, Nurisa; Retnowati, Rita; Sunaryo, Widodo (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aimed to analyze the relationship between transformational leadership and learning organization to teacher creativity. The research approach used is quantitative with a correlational type. The population of this research is all civil servant teachers at state elementary schools in Cijeruk District-Bogor, totaling 155 teachers. Sampling used a proportional random sampling technique with a total sample of 112 teachers. This research uses quantitative data and data sources consisting of primary data (respondents) and secondary data (books, relevant journals, and so on). Data collection techniques using a questionnaire. There are three questionnaire data: transformational leadership, learning organization, and teacher creativity. Data analysis techniques are normality, homogeneity, and linearity tests. The research results obtained the following conclusions: (1) There is a positive relationship between transformational leadership and teacher creativity with a correlation coefficient ry.1=0.368 and the functional relationship equation Ŷ= 6.716 + 0.861X1. Transformational leadership contributes 13.5% to teacher creativity. (2) There is a positive relationship between learning organization and teacher creativity with correlation coefficient ry.2=0.796 and functional relationship equation ŶŶ= -15.225 + 0.978X2. Learning organizations contribute 63.3% of teacher creativity. (3) There is a positive relationship between transformational and learning organization together with teacher creativity with a correlation coefficient R= 0.808 and functional relationship equation Ŷ= -58.672 + 0.340X1 + 0.925X2. The contribution of transformational leadership and learning organization together with teacher creativity means that the better transformational leadership and learning organization, the better teacher creativity will be.